Structure-guided engineering of immunotherapies targeting TRBC1 and TRBC2 in T cell malignancies - Mathieu Ferrari; Matteo Righi; Vania Baldan; Patrycja Wawrzyniecka; Anna Bulek; Alexander Kinna; Biao Ma; Reyisa Bughda; Zulaikha Akbar; Saket Srivastava; Isaac Gannon; Mathew Robson; et al. (Nature Communications, 2024)
Abstract Peripheral T cell lymphomas are typically aggressive with a poor prognosis. Unlike other hematologic malignancies, the lack of target antigens to discriminate healthy from malignant cells limits the efficacy of immunotherapeutic approaches. The T cell receptor expresses one of two highly homologous chains [T cell receptor β-chain constant (TRBC) domains 1 and 2] in a mutually exclusive manner, making it a promising target. Here we demonstrate specificity redirection by rational design using structure-guided computational biology to generate a TRBC2-specific antibody (KFN), complementing the antibody previously described by our laboratory with unique TRBC1 specificity (Jovi-1) in targeting broader spectrum of T cell malignancies clonally expressing either of the two chains. This permits generation of paired reagents (chimeric antigen receptor-T cells) specific for TRBC1 and TRBC2, with preclinical evidence to support their efficacy in T cell malignancies.